Vertical Jump and Relative Strength are Strongly Associated with Change of Direction in Professional Male Basketball Players - Stefano Benitez Flores; Eduardo Lusa Cadore; Emilija Stojanović; Anne Delextrat; Julio Calleja-González (International Universities Strength and Conditioning Association, 2024)
Purpose: The aim of this study was to examine the predictors of change of direction (COD) in highly trained/national level male basketball players using field assessments. Methods: Eight professional male basketball players (age: 24.0 ± 5.5 years; body mass index (BMI): 24.1 ± 1.6 kg m-2) volunteered for participation in this study. All the evaluations were carried out during 2 sessions as follows: First day_1) body composition, 2) unilateral and bilateral squat jump (SJ) and countermovement (CMJ), and 3) Yo-Yo intermittent recovery test level 1 (Yo-Yo IR1); Second day_1) COD performance, and 2) one repetition maximum (1RM) hang clean (HC) and bench press (BP). A linear regression was performed to evaluate the determinants of COD amongst all other measured variables. Furthermore, we applied Pearson correlation coefficient and in the case of non-normally distributed variables, Spearman's correlation coefficient for the selected variables. Results: The linear regression indicated that only SJ height was a significant determinant of COD (R2 = 58.8%, p = 0.016). Significant correlations were identified between COD test and SJ (r = -0.75, p = 0.034; very large), and relative HC 1 RM (r = -0.74, p = 0.038; very large). Conclusions: The associations found between COD performance and physical parameters should be considered when developing athletic conditioning programs. Especially, the vertical jump heigh could explain the greatest variability in COD performance..